(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
أجريت هذه الدراسة للحصول على أسرع إنبات، وأعلى إنتاج من البادرات ومجموع خضري وجذري متطورين بشكل جيد , واستخدمنا في الدراسة المعاملات الآتية: تجربة المعاملة بحمض الكبريت المركز مدة ساعة واستعملت لها 200 بذرة , 100 بذرة زرعت في التربة المنقولة من الغابة , و100 بذرة زرعت في تربة المشتل , وتجربة المعاملة بالماء المغلي تقريبا ْ80 وشملت 200 بذرة زرعت 100 بذرة منها في التربة المنقولة من الغابة و100 بذرة في تربة المشتل أيضا ، إضافة إلى ذلك تم زرع 100 بذرة منقوعة بالماء الساخن واستخدمت شاهداً. أظهرت نتائج الدراسة نجاح طريقة المعاملة بحمض الكبريت المركز مدة ساعة وتفوقها في رفع نسبة إنتاش بذور الخرنوب إلى 82% وتسريعه ، كما بينّت النتائج أن لتربة الغابة الأثر الأكبر في نمو المجموع الجذري للبادرات وتطوره قياساً بالمعاملات الأخرى . This study was conducted in order to obtain the fastest germination, the highest rate of seedling production and a well developed vegetation and radical total. In this study, we used the following coefficients: Being sulfur acid treatment concentreted for an hour and we used 200 seeds. 100 seeds planted in soil transported from the forest and 100 seeds planted in the soil of the nursery. Being treated with boiling water about 80 degrees Celsius. The study included 200 seeds, 100 seed were planted in soil transported from the forest and 100 seeds were planted in the soil of the nursery. In addition, 100 seeds soaked in hot water were planted and used as a control. The results showed the success of the sulfuric acid concentrated method for an hour and the superiority in raising the proportion of germination seeds with the husks to 82% and accelerating it. Results also showed that the soil of forests has the greatest impact on the growth and development of roots for seedlings compared to other treatments.